The Role of Teachers, Students and Curriculum in Classical Islamic Education - Febrian, M Agil; Repi, Predi Ari; Yulia, Fatma (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This article discusses the role of teachers, students, and curriculum in the context of classical Islamic education, with a focus on literature analysis from various primary and secondary sources. The main aim of this writing is to describe the contribution of each entity in building a solid foundation for Islamic education. Teachers in classical Islamic education are considered the main pillars in transmitting religious and moral knowledge, while students act as recipients of knowledge who are responsible for understanding and applying these teachings in everyday life. The curriculum in this context is designed to ensure a thorough understanding of Islamic spiritual and ethical values, as well as to develop students' critical thinking. This research methodology involves a comprehensive literature study, analyzing classical texts and secondary literature to explore the relevance and application of educational concepts in the classical Islamic tradition. Thus, this study is expected to provide in-depth insight into the roles played by teachers, students, and curriculum in classical Islamic education and their relevance in the context of modern education